Pemberdayaan Masyarakat Melalui Penyuluhan Hukum dan Pengelolaan Sampah di Paguyuban Blok EM Rogojampi Banyuwangi - Nuri Hidayati; Muhammad Zulqurnain; Reny Eka Evi Susanti (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
Household waste management remains a critical issue in Indonesia, with far-reaching impacts on the environment, public health, and socio-economic well-being. Rogojampi Village, Banyuwangi, is among the affected areas, as reflected in the accumulation of waste in the Dam Concrong River that leads to environmental degradation. This community engagement program was designed to empower local residents through a participatory approach to household waste management by integrating regulatory education, hands-on training, adoption of simple technologies, and continuous mentoring. The training focused on the production of bag compost, anaerobic bucket compost, local microorganisms (MOL), and eco-enzyme solutions, all of which were directly practiced by participants. The results indicated substantial improvements in community knowledge and technical capacity, as participants successfully transformed organic waste into valuable products such as compost, MOL biofertilizers, and eco-enzyme liquids for household and agricultural use. Furthermore, the program encouraged the establishment of a village waste management group and introduced the waste bank concept as a long-term sustainability strategy. Besides reducing organic waste accumulation, the initiative also created economic opportunities through the valorization of recyclable inorganic waste. In conclusion, the combination of participatory methods, MOL-based bioproducts, eco-enzyme technology, and continuous assistance proved effective in shifting community behavior from waste disposal to waste utilization, thereby contributing to the achievement of Sustainable Development Goals (SDGs).